ETIOLOGICAL STRUCTURE OF ACUTE OBSTRUCTIVE BRONCHITIS IN CHILDREN (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Active identification of etiological factors of respiratory infections and development of criteria for timely diagnosis and treatment is, from the position of clinical bronchology, a promising scientific direction.